Proposed Decision Making in Pricing Strategy Selection for New Vaccine Packaging Study of PT Bpharmaceutical - Nadia Alifya Zahra; Santi Novani (Publikasi Indonesia, 2025)
This study is conducted to develop a structured approach for selecting the most viable pricing strategy for Vaccine T packaging transformation from ampoules to prefilled syringes (PFS), which is a tetanus-diphtheria vaccine produced by PT BPharmaceutical. The packaging innovation is intended to improve dosage accuracy, reduce contamination risks, and align with market trends. To overcome this challenge, this study uses the Analytical Hierarchy Process (AHP) to evaluate and assess the selection of the most suitable pricing strategy based on key financial considerations. The research employs both qualitative and quantitative methods and is grounded in both primary and secondary data. Internal interviews, FGD, and a questionnaire were conducted with the company’s stakeholders to identify relevant pricing criteria, SWOT analysis, and possible strategy alternatives. External and internal analyses were also performed through PESTEL, Porter’s Five Forces, STP, demand forecasting, and SWOT-TOWS matrix to identify the decision-making environment. Based on these inputs, three strategic alternatives were formulated: Skimming, Penetration, and Strategic. These alternatives were then assessed using AHP based on three main criteria: price changes, average cost per unit, and cost recovery. Price changes have two sub-criteria: average yearly price increase and average gross profit margin, while cost recovery has three sub-criteria: NPV, IRR, and PBP. The result from the AHP analysis indicated that the Strategic pricing strategy is the most viable option, with the highest score of 0.029. An implementation roadmap has also been developed to ensure the strategic execution of this pricing decision.